Marketing Counseling for Handicraft Business from Plastic Waste through TikTok Digital Platform for Community Empowerment of Nusantara Tourism Village (Puspamukti Village) - Nurherawati; Pramesti Melyna Mustofa; Ardiansyah; Alfin Nur Arifah; Della Apriani (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
Puspamukti Village is a Tourism Village that has various potentials in various fields, both agriculture and plantations. Puspamukti villagers are housewives who have free time besides farming and gardening. This counseling aims to empower the Puspamukti Village community through the development of a handicraft business from unused plastic waste that has been converted into goods that have selling power by making Profitable Trash, namely ceramics from garbage that has aesthetic value and marketable functions by utilizing the TikTok digital platform. The method used is a method with counseling activities including product manufacturing training, digital marketing techniques, and branding strategies. The results showed an increase in community knowledge and skills in managing plastic waste into value-added products, as well as an increase in community interest in marketing their products through TikTok. In addition, this counseling also succeeded in building a network between handicraft business actors in Puspamukti Village with a wider potential buyer. It can be concluded that the activities for community empowerment in Puspamukti Village have achieved a number of successes, including: 1) Increased awareness and skills: Puspamukti villagers have a better understanding of plastic waste management and are able to produce value-added handicraft products; 2) Behavior change: There have been positive behavioral changes in the community, namely an increased interest in processing plastic waste into useful products; 3) Economic development: The plastic waste handicraft business has the potential to increase community income and contribute to the village economy; 4) Effectiveness of TikTok utilization: The TikTok platform has proven effective as a promotional and marketing medium for handicraft products.